(untitled) - INSYIANI ZANAH, RIFQO (Language Horizon: Journal of Language Studies, 2015)
Abstrak Perkembangan Bahasa non-standard Ingrris menjadi ideologi yang muncul dalam hubungan sosial dan berlaku di komunitas – komunitas dengan hubungan yang baik (Coupland, 2007). Hal ini, bisa dilihat dari video Daniel Howell dimana Bahasa non-standard Inggrisnya mengalami perubahan. Dari dua video Daniel Howell berjudul “Hello Internet” (2009) dan “Draw My Life” (2013), artikel ini membahas analisis dari fitur – fitur linguistic yang berbeda di kedua video dan kenapa perbedaan tersebut dapat terjadi. Descriptive qualitative adalah metode yang digunakan dalam penelitian ini. Pengumpulan data dilakukan dengan mengelompokkan dan menganalisa kalimat Bahasa non-standard Inggris dari kedua video. Alat yang digunakan adalah peneliti sendiri yang menggunakan laptop, pemutar video VLC, dan earphone untuk membantu peneliti dalam mengumpulkan data. Hasil penelitian menunjukkan bahwa terdapat 4 fitur linguistic yang terjadi; fonologi, morphologi, syntax, dan lexical. Di fitur fonologi antara lain; realization of final /?/, the velar nasal, as the alveolar nasal /n/; -r deletion; final consonant cluster reduction; devoicing; and the change of vowel sound. Kata kunci: Non-standard, Youtubers, Daniel Howell. Abstract Non-standard maintenance later becomes an ideology which is work within social network, and it usually operates in tight communities (Coupland, 2007). This can be seen in Daniel Howell’s videos in which his non-standard English Language experiencing the changes. From Daniel Howell’s video “Hello Internet” (2009) and “Draw My Life” (2013), this research tries to analyse what linguistic features differ from both of the videos and why the distinction of non-standard language between both of the videos occur. Descriptive qualitative method is used in this research. The data collection was done by gathering and analysing every sentence which contain of non-standard features of English by Daniel Howell. The instrument was the researcher himself who uses a laptop, VLC player, and the earphone to help the researcher to collect the data. The finding of the research show that there are four linguistic features acquired by Daniel Howell, they are phonological, morphological, syntactical, and lexical. In phonological features, there are realization of final /?/, the velar nasal, as the alveolar nasal /n/; -r deletion; final consonant cluster reduction; devoicing; and the change of vowel sound. Keywords: Non-standard, Youtubers, Daniel Howell.